Berberine Induces Autophagic Cell Death in Acute Lymphoblastic Leukemia by Inactivating AKT/mTORC1 Signaling - Liu J; Liu P; Xu T; Chen Z; Kong H; Chu W; Wang Y; Liu Y (Dove Medical Press, 2020)
Jian Liu,1 Peng Liu,2 Tiantian Xu,1 Zhiwei Chen,1 Huimin Kong,1 Weihong Chu,1 Yingchao Wang,1 Yufeng Liu1 1Department of Pediatrics, The First Affiliated Hospital of Zhengzhou University, Zhengzhou 450052, People’s Republic of China; 2Department of Pediatric Intensive Care Unit, The First Affiliated Hospital of Zhengzhou University, Zhengzhou 450052, People’s Republic of ChinaCorrespondence: Jian LiuThe First Affiliated Hospital of Zhengzhou University, 1 East Jianshe Road, Zhengzhou 450052, People’s Republic of ChinaEmail liujian018@qq.comIntroduction: Berberine has been reported to inhibit cancer cell growth by apoptosis induction and exhibits a protective role against cancer progression. The current study aims to investigate the effects of berberine on acute lymphoblastic leukemia (ALL) and the mechanism beyond apoptosis.Methods: Cell viability was determined in ALL cell lines EU-6 and SKW-3 using trypan blue staining. Cell autophagy was determined by immunofluorescence and Western blot. ALL xenograft mice were established to investigate the anti-tumor effects of BBR. The molecular mechanism was explored in ALL cell lines using siRNA and signaling inhibitors.Results: Herein, we show that berberine treatment significantly inhibits ALL cell viability and promotes cell death by inducing autophagy in a dose-dependent manner. Moreover, berberine significantly alleviates the aggressive pathological condition in ALL xenograft mice. Mechanistic studies exhibit that berberine induces autophagic death in ALL cells by inactivating AKT/mTORC1 signaling. Chemically targeting AKT/mTORC1 signaling controls berberine-induced cell autophagy in vitro, and blockade of autophagic process blunts berberine-alleviated pathological condition in vivo.Discussion: In conclusion, our study reveals that berberine could induce ALL cell autophagic death by inactivating AKT/mTORC1 signaling that could be used to develop small molecule drug for ALL treatment.Keywords: acute lymphoblastic leukemia, berberine, AKT/mTORC1, autophagy